2022
DOI: 10.1111/jch.14424
|View full text |Cite
|
Sign up to set email alerts
|

The association of hypertriglyceridemic waist phenotype with hypertension: A cross‐sectional study in a Chinese middle aged‐old population

Abstract: The present study aimed to evaluate the relationship between the hypertriglyceridemic waist (HTGW) phenotype and hypertension. We undertook a cross-sectional study with a sample of 9015 adults from China. The HTGW phenotype was defined as elevated waist circumference (WC) and elevated triglyceride (TG) concentration.Logistic regression analysis was used to evaluate the association between the HTGW phenotype and hypertension. The prevalence of hypertension was significantly higher in individuals with the HTGW p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
2
7
0
Order By: Relevance
“…Our HTGW subjects had a significantly higher prevalence of hyperuricemia (67.6%) compared to those with NWNT phenotype (44.9%). This corroborates findings from similar studies [16,27,28]. The high prevalence of hyperuricemia in the HTGW phenotype agrees with the reported finding that elevated serum uric acid is associated with the metabolic syndrome, of which the HTGW phenotype is a surrogate of [46][47][48].…”
Section: Plos Global Public Healthsupporting
confidence: 92%
See 2 more Smart Citations
“…Our HTGW subjects had a significantly higher prevalence of hyperuricemia (67.6%) compared to those with NWNT phenotype (44.9%). This corroborates findings from similar studies [16,27,28]. The high prevalence of hyperuricemia in the HTGW phenotype agrees with the reported finding that elevated serum uric acid is associated with the metabolic syndrome, of which the HTGW phenotype is a surrogate of [46][47][48].…”
Section: Plos Global Public Healthsupporting
confidence: 92%
“…Our study also demonstrated greater aggregation of metabolic perturbations in the HTGW phenotype, which has been demonstrated by other studies [14][15][16]. The direct implication of this perturbations is a heightened risk of CVD, prospectively [29][30][31].…”
Section: Plos Global Public Healthsupporting
confidence: 87%
See 1 more Smart Citation
“…The hypertriglyceridemic-waist phenotype, defined as elevated TG and enlarged WC, was a simple marker of visceral adiposity [ 15 ]. Previous studies indicated that HTGW was associated with higher risk of diabetes, hypertension, and cardiovascular diseases [ 20 22 , 40 , 41 ]. A meta-analysis further indicated that HTGW was closely associated with an increased risk of diabetes in the general population [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…13 The HTGW phenotype has advantages in assessing individuals with higher risk of metabolic abnormalities compared with elevated TG or enlarged WC used alone. 14 Furthermore, several epidemiological studies showed the strong positive correlations of the HTGW phenotype with the risk of CVD, 15,16 prediabetes and diabetes, 17,18 hypertension, 19,20 and hyperuricemia. 21 Other studies reported the association of HTGW phenotype with an increasing risk of CKD in general middle-old adults 22,23 and in lean people (BMI < 24 kg/m 2 ).…”
Section: Introductionmentioning
confidence: 99%